HEARTS initiative for the prevention and control of high blood pressure in the community of Paján in Ecuador - Véliz, Sofía D.; Toro, Melanie D.; Revilla, Mario A.; Asanza, Diana J.; Demera, Jordan J.; Saldarriaga, Freddy B.; Pinargote, Patricia P. (Revista Gregoriana de Ciencias de la Salud, 2025)
Cardiovascular diseases are the leading cause of morbidity and mortality worldwide, with high blood pressure (HBP) being its main modifiable risk factor. In response to this problem, the World Health Organization and the Pan American Health Organization developed the HEARTS initiative. This study aimed to analyze the HEARTS initiative in the community of Paján, Ecuador, evaluating its effectiveness in the prevention and control of HBP from a comprehensive approach based on primary care. A descriptive, cross-sectional, and observational methodology was employed, utilizing structured surveys and semi-structured interviews to analyze participants’ perceptions regarding access to the program, adherence to treatment, and difficulties in controlling HBP. The results indicate the need to strengthen the dissemination of the program and improve access to medications to ensure its effectiveness in the community.